Challenges and emerging opportunities for the HIV prevention, treatment and care cascade in men who have sex with men in Asia Pacific. (20th July 2017) - van Griensven, Frits; Guadamuz, Thomas E; de Lind van Wijngaarden, Jan Willem; Phanuphak, Nittaya; Solomon, Sunil Suhas; Lo, Ying-Ru
Abstract : In Asia Pacific, most countries have expanded HIV treatment guidelines to include all those with HIV infection and adopted antiretroviral treatment for prevention (TFP) as a blanket strategy for HIV control. Although the overall epidemic development associated with this focus is positive, the HIV epidemic in men who have sex with men (MSM) is continuing unperturbed without any signs of decline or reversal. This raises doubt about whether TFP as a blanket HIV prevention policy is the right approach. This paper reviews currently available biomedical HIV prevention strategies, national HIV prevention policies and guidelines from selected countries and published data on the HIV cascade in MSM. No evidence for efficacy of TFP in protecting MSM from HIV infection was found. The rationale for this approach is based on assumptions about biological plausibility and external validity of latency-based efficacy found in heterosexual couples. This is different from the route and timing of HIV transmission in MSM. New HIV infections in MSM principally occur in chains of acutely HIV-infected highly sexually active young men, in whom acquisition and transmission are correlated in space and time. By the time TFP renders its effects, most new HIV infections in MSM will have already occurred. On a global level, less than 6% of all reports regarding the HIV care cascade from 1990 to 2016 included MSM, and only 2.3% concerned MSM in low/middle-income countries. Only one report originated from Asia Pacific. Generally, HIV cascade data in MSM show a sobering picture of TFP in engaging and retaining MSM along the continuum. Widening the cascade with a preventive extension, including pre-exposure prophylaxis, the first proven efficacious and only biomedical HIV prevention strategy in MSM, will be instrumental in achieving HIV epidemic control in this group.